Pentingnya Kerjasama (Partnership) dalam Pelayanan Kesehatan di Lembaga Pemasyarakatan - Putri Indraswari Susilo; Padmono Wibowo (CV. Syntax Corporation Indonesia, 2021)
The purpose of this study is to find out and explain how the implementation of the fulfillment of the rights and obligations of the State in the fulfillment of the right to health services for inmates. This research is a type of legal research with normative approach. The implementation of the rights of inmates in the field of health services as guaranteed by the State as a human right through Law No. 12 of 1995 that has not been carried out optimally with the obstacles of lack of human resources, namely medical personnel. By reviewing the relationship of cooperation (partnership) in the fulfillment of health services in correctional institutions. health services in correctional institutions are; the right of availability, the right of affordability, the right to receive and the right to quality of health services Implementation of the fulfillment of the right to health services for inmates.